ITOCHU : a Japanese firm in the era of retrenchment and reform - Zhu, Ying, 1961- (SAGE knowledge. Cases., 2016)
ITOCHU is used here as an example of recent HR retention and training development. The company, which was founded in 1858 and grew over the years, changes the HR retention policies focusing on specialization instead of job rotation, in order to attract capable young people to join the organisation and promote long-term commitment.